[BH3C(NO2)3]−: The First Room‐Temperature Stable (Trinitromethyl)borate1. Issue 42 (27th August 2013) - Bélanger‐Chabot, Guillaume; Rahm, Martin; Haiges, Ralf; Christe, Karl O.
<x xml:space="preserve">Abstract</x> The marriage of fire and water: The strongly oxidizing trinitromethyl and strongly reducing BH3 groups were successfully combined for the first time in the novel [BH3C(NO2)3]− ion. The stability at room temperature of the new (trinitromethyl)borate is in sharp contrast to the behavior of [BCl3C(NO2)3]−, which already decomposes at −20 °C.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>